Progenitor effect in the spleen drives early recovery via universal hematopoietic cell inflation - Takao Yogo; Hans Jiro Becker; Takaharu Kimura; Satoshi Iwano; Takahiro Kuchimaru; Atsushi Miyawaki; Tomomasa Yokomizo; Toshio Suda; Atsushi Iwama; Satoshi Yamazaki (Cell Reports)
Summary: Hematopoietic stem cells (HSCs) possess the capacity to regenerate the entire hematopoietic system. However, the precise HSC dynamics in the early post-transplantation phase remain an enigma. Clinically, the initial hematopoiesis in the post-transplantation period is critical, necessitating strategies to accelerate hematopoietic recovery. Here, we uncovered the spatiotemporal dynamics of early active hematopoiesis, “hematopoietic cell inflation,” using a highly sensitive in vivo imaging system. Hematopoietic cell inflation occurs in three peaks in the spleen after transplantation, with common myeloid progenitors (CMPs), notably characterized by HSC-like signatures, playing a central role. Leveraging these findings, we developed expanded CMPs (exCMPs), which exhibit a gene expression pattern that selectively proliferates in the spleen and promotes hematopoietic expansion. Moreover, universal exCMPs supported early hematopoiesis in allogeneic transplantation. Human universal exCMPs have the potential to be a viable therapeutic enhancement for all HSC transplant patients.